An Exploratory Study Of Parental Savings For Higher Education - Noraina Mazuin Sapuan (Universiti Sains Islam Malaysia, 2015)
The cost of higher education (HE) has increased dramatically in recent years especially in private universities. At the same time, very limited amounts of government's scholarships and loans available for pursuing HE. One of the alternative for financing sources is parental saving. However, it has been reported that there is low awareness level among parents on the importance of saving for their children HE. This study attempts to explore on parental saving for children's HE among parents based on their different demographic characteristics. A convenient sampling method was applied to conduct a survey among parents in Pahang. This study measures two variables: first, parents' savings behavior, and second, savers' confidence level in continuing their savings for children's HE. The Findings of this study revealed that many parents aware of the importance to start saving for their children HE since their early childhood. There is a positive correlation between savings behavior with respondents' income level, value of assets owned, occupation, level of education and confident level. The result also revealed that the savers' confidence level is positively correlated with income level, occupation, saving behavior, education level and value of assets owned. Its is hoped that the findings from this study will give directions for additional research parental savings for HE, of which there is currently very little especially in Malaysia.